Two new cases with novel pathogenic variants reflecting the clinical diversity of Schaaf-Yang syndrome - ALAVANDA, CEREN; GEÇKİNLİ, BİLGEN BİLGE; DEMİRCİOĞLU, SERAP; ARMAN, AHMET (My University, 2023)
Schaaf-Yang syndrome (SHFYNG) is a rare pleiotropic disorder, characterized by hypotonia, joint contractures, autism spectrum disorders (ASD), and developmental delay/intellectual disability. Although it shares some common features with Prader-Willi Syndrome, joint contractures, and ASD were more commonly detected in in this syndrome. Recently, it was shown that truncating variants in the paternal allele of the MAGEL2 gene cause SHFYNG. Here, we present two patients diagnosed with SHFYNG syndrome having two different novel truncating variants in the MAGEL2 gene, one paternally inherited and one de novo. One patient had obesity, brachydactyly and dysmorphic features, and the other patient presented with contractures, severe hypotonia and early death. This is the first report of Turkish SHFYNG syndrome cases presented to emphasize the phenotypic diversity of the syndrome.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; GENETICS & HEREDITY; Genetik; Genetik (klinik); Genetics; Genetics (clinical); MAGEL2; novel; Prader-Willi-like syndrome; Schaaf-Yang syndrome; SHFYNG; MAGEL2; novel; Prader-Willi-like syndrome; Schaaf-Yang syndrome; SHFYNG